Свойства спеченных материалов из губчатых порошков титана - Савич, В.В. (Вісник Українського матеріалознавчого товариства, 2016)
Based on the analysis of literature and own research results, methods for the control parameters of porous structure of the sintered porous material from the sponge titanium powder identified and recommended: molding charge by using volatilizing blowing agent under sintering; the use of the charge from the mixture of spherical and spongy particles; molding by applying pressure to the powder application phase through elastic envelope or trim of the punch. To control the micro- and macrostructures parameters, the chemical or electrochemical machining of sintered samples and products which allow increasing the thickness of an oxide layer on the surfaces of pores, as well as modifying the texture of ths layer up to a nanoscale level has been recommended.